Tracking Human Immunodeficiency Virus-1 Infection in the Humanized DRAG Mouse Model - Kim, Jiae; Peachman, Kristina K.; Jobe, Ousman; Morrison, Elaine B.; Allam, Atef; Jagodzinski, Linda; Casares, Sofia A.; Rao, Mangala (Frontiers in Immunology, 2017)
Humanized mice are emerging as an alternative model system to well established nonhuman primate (NHP) models for studying HIV-1 biology and pathogenesis. Although, both NHP and humanized mice have their own strengths and could never truly reflect the complex human immune system and biology, there are several advantages of using the humanized mice in terms of using primary HIV-1 for infection instead of SIV or SHIV. Several different types of humanized mice have been developed with varying levels of reconstitution of human CD45+ cells. In this study, we utilized humanized Rag1KO.IL2RγcKO.NOD mice expressing HLA class II (DR4) molecule (DRAG mice) infused with HLA-matched hematopoietic stem cells from umbilical cord blood to study early events after HIV-1 infection, since the mucosal tissues of these mice are highly enriched for human lymphocytes and express the receptors and coreceptors needed for HIV-1 entry. We examined the various tissues on days 4, 7, 14, and 21 after an intravaginal administration of a single dose of purified primary HIV-1. Plasma HIV-1 RNA was detected as early as day 7, with 100% of the animals becoming plasma RNA positive by day 21 post-infection. Single cells were isolated from lymph nodes, bone marrow, spleen, gut, female reproductive tissue, and brain and analyzed for gag RNA and strong stop DNA by quantitative (RT)-PCR. Our data demonstrated the presence of HIV-1 viral RNA and DNA in all of the tissues examined and that the virus was replication competent and spread rapidly. Bone marrow, gut, and lymph nodes were viral RNA positive by day 4 post-infection, while other tissues and plasma became positive typically between 7 and 14 days post-infection. Interestingly, the brain was the last tissue to become HIV-1 viral RNA and DNA positive by day 21 post-infection. These data support the notion that humanized DRAG mice could serve as an excellent model for studying the trafficking of HIV-1 to the various tissues, identification of cells harboring the virus, and thus could serve as a model system for HIV-1 pathogenesis and reservoir studies.